2018
DOI: 10.22502/jlmc.v6i2.212
|View full text |Cite
|
Sign up to set email alerts
|

Etiological Profile and Neurodevelopment Outcome of Neonatal seizure

Abstract: IntroductionNeonatal seizures are the most common manifestation of neurological disorders in newborn period. It is an important determinant of outcome as well. This study aims to delineate the etiological profile and neurodevelopmental outcome of neonatal seizure. It is also aimed to identify the predictors of neurodevelopmental outcome in survivors. MethodsWe recruited consecutively 117 neonates with clinically proven seizures admitted in XXXXX hospital, between February 2014 to February 2016. All of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…In our study it was also found that; 69.7% of new-borns had an early-onset seizure which occurs before 72 hours. This finding is comparable to the findings in the study by Shah et al, 9 Rastogi et al's study (66.67%), 4 Dongol Singh et al's study (70.9%), 15 and Baudou et al's study (78%). 18 The explanation is as perinatal asphyxia is the most common comorbidity in those studies and seizures in perinatal asphyxia are usually early onset.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study it was also found that; 69.7% of new-borns had an early-onset seizure which occurs before 72 hours. This finding is comparable to the findings in the study by Shah et al, 9 Rastogi et al's study (66.67%), 4 Dongol Singh et al's study (70.9%), 15 and Baudou et al's study (78%). 18 The explanation is as perinatal asphyxia is the most common comorbidity in those studies and seizures in perinatal asphyxia are usually early onset.…”
Section: Discussionsupporting
confidence: 89%
“…Our study found that the burden of neonatal seizures was 9.6% of neonatal admissions, which is comparable to the finding of Shah et al's study (9.95%) 9 and Mwaniki et al's study (9%) 6 but slightly lower than the results of Dongol Singh et al's study (12.26%) 15 and Sudia et al's study (11.7%). 16 This low incidence can be because we were only able to document clinically obvious seizures and we did not practice diagnostic EEG recording for neonates who are at risk of seizure which possibly subclinical seizures can be missed.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The odds of developing neonatal seizure were nearly six times higher in neonates admitted within 24 hours of birth as compared to neonates 7-28 days old. This aligns with a study conducted in Landon (17), Kathmandu University in Dhulikhel (18), the University of Gonder in Ethiopia (12), and Dhaka Medical College in India (15). This is because immediately after birth, neonates are challenged with an extra uterine environment, and their organs such as the brain are not completely grown.…”
Section: Discussionsupporting
confidence: 86%